An evaluation of ultraviolet germicidal irradiation (UVGI) technology in health care facilities - Dreiling, Jeremy B. (Kansas State University, 2008)
Health care facilities are responsible for treating highly infected and contagious patients at the same time as patients who are most susceptible to disease. Therefore, it is important that every available technology and application to be strategically applied to protect each and every occupant. In particular, ultraviolet germicidal irradiation (UVGI) technologies are being used in today's industry as infection control devices, primarily in health care facilities. This paper addresses the effectiveness and economic impact of applying UVGI to remove harmful airborne pathogens and outlines background information on infectious airborne pathogens such as viruses, bacteria, and fungi. Besides UVGI, other engineering control methods covered in this paper include mechanical ventilation and air distribution, filtration, and differential pressure control. Consequently, an economic evaluation of a diagnostic and treatment area was created to compare UVGI technologies and other control methods. The evaluation consists of a baseline system designed to meet code requirements; an upper-room UVGI system; a heating, ventilating, and air-conditioning (HVAC) system with an increased air changes per hour (ACH); and a UVGI system in an AHU. First costs, energy costs, and maintenance costs were the basis of economic comparison. The predicted effectiveness of all the alternatives was held constant and the time required to achieve the desired effectiveness was determined. As a result, the upper-room UVGI system and HVAC system with an increased ACH yielded much higher comparative annual costs as well as significantly better room disinfection effectiveness. The UVGI system in the AHU resulted in a lower comparative annual cost than the baseline system with the same room disinfection effectiveness. By designing infection control systems with UVGI, HVAC engineers will be more capable and successful in providing the optimal control system to these critical facilities.
Keywords: Ultraviolet germicidal irradiation; Health care; Nosocomial infections; Economic analysis; Engineering control methods; Pathogens; Engineering, Mechanical (0548)